Pola Komunikasi Figur Perempuan dalam Kepemimpinan Pendidikan Islam - Ditha Prasanti (Jurnal Komunikasi Global, 2017)
Good Islamic education leadership also requires good communication competence between leaders with their members. This can be seen from the leader's communication pattern in applying Islamic education leadership in his educational institution. In this era of modern society, it is familiar to see more women become leaders in their organization in Indonesia. The author examines the communication patterns of female figures in the leadership of Islamic education in the institution of Early Childhood Education (PAUD) in Bandung. This research uses a qualitative research method of a case study by conducting observations and in-depth interviews with five informants. The results of this study indicate that the communication pattern of the female figure in Islamic education leadership in the institution has certain characteristics that are different from other institutions. The verbal communication pattern conducted by the principal through the secretary uses a verbal language that implements Islamic teachings. In this early childhood institution, all decisions are held by the secretary because of Islamic values, the man who has the authority to give a decision on all activities in the early childhood. Nonverbal communication pattern in the form of Islamic nonverbal message applied by the principal through the concept of smile, regards, greetings, and courtesy become a culture within the institution of Islamic education.